Trans materialist critique as feminist practice: lessons from a polemic against nonbinary identities - Llaveria Caselles, Eric (Frontiers in Sociology, 2025)
This article explores the tensions between trans materialist critique and nonbinary identities, using Kadji Amin’s essay “We Are All Nonbinary: A Brief History of Accidents” (2022) as a point of departure. It asks two guiding questions: How should we understand the relationship between trans and nonbinary identities? And what kind of trans materialism can meaningfully respond to our current political moment? The article focuses on three problematics: (1) the reliance on abstract philosophical critiques of gender identity; (2) the framing of trans and nonbinary identities as objective versus subjective, respectively; and (3) the portrayal of nonbinary identity as emblematic of neoliberal ideology. Drawing on posttranssexual (Susan Stryker, Sandy Stone), travesti (Lohana Berkins, Marlene Wayar), and nonbinary (Eris Young, Travis Alabanza) narratives—as well as critical feminist theory (Judith Butler, Nancy Fraser, Seyla Benhabib, Regina Becker-Schmidt)—the article argues for understanding gender identity claims as situated political practices that are simultaneously subjectively and objectively constituted. It critiques positivist tendencies within trans materialism and challenges polarizing distinctions between trans and nonbinary identities. Ultimately, it builds on Wendy Brown's definition of neoliberalism to argue that dismissing nonbinary identities on materialist grounds risks constructing the trans critic as a neutral subject outside power, becoming another site for the hollowing out of democratic practice. The article calls for a trans materialism grounded in self-critical feminist analysis and relational political practice.